PERANCANGAN ULANG SISTEM HVAC PADA GEDUNG PERKANTORAN X DI JAKARTA DENGAN METODE CLTD - Mohamad Faizal; Rudi Saputra (Bina Teknika, 2016)
HVAC system ( Heating Ventilating and Air Conditioning ) is a system that serves to organize temperatures and humidity the air on a room , that feels comfortable condition. In redesigned system HVAC to 8 floors office buildings , by using CLTD method ( cooling load temperature difference ), where the state of temperature design at 73,4 and 50% moisture. Existing cooling load 8.880.000 BTU/hr and air supply existing of 264.180 CFM. Redesigned calculation of cooling load is 11.626.701 BTU/hr ,where there is increased by 30.9 %, and obtained needs air supply of 343.456,73 CFM and increased by 30 %. Chiller system installation at the building using air cooled chiller , existing chiller using four chiller units of 250 tons refigerant each and one units for back up. Based of calculation obtained chiller capacity is 969 tons refrigerant, so that four units chiller available must in operates with 17 Air Handling Unit (AHU) to be optimum cooling,with dimension ducting 35 in the largest and smallest 9,5 in.